Factors That Predict the Level of Internationalization of Small and Medium Mexican Export Companies - Ibarra-Morales, Luis Enrique; Buenrostro Aguilar, Hugo Javier; Paredes-Zempual, Daniel; Farah Simon, Lisette (European Scientific Journal, ESJ, 2025)
Globalization has led exporting companies to design and implement strategies to increase their presence in international markets; however, it is necessary to have a greater understanding of the factors that determine the level of internationalization, since literature alone does not provide sufficient and specific information for decision-making. The objective is to determine which variables predict the level of internationalization of Mexican export companies, by validating a random sample with 119 export companies from the state of Sonora. The methodology was descriptive with a quantitative approach. The information was processed and analyzed in the SPSS program using the ordinal logistic regression model. The results support that the price of the product, the installed capacity, and the commercial agreements are significant variables that directly predict the level of internationalization of companies, concluded that they are important for the growth, diversification, and permanence of an international market to implement mechanisms to improve exports by their resources and capacities. This can be taken up again in subsequent studies and a practical sense in the exporting companies by promoting exporters’ actions that encourage new procedures, processes, and products that allow a monetary impact on them.